ACACIA SENEGAL BARK EXTRACT IN REGULATION OF HYPOTHYROIDISM: AN EXPERIMENTAL APPROACH - Jangid, Dheeraj; Purohit, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to evaluate the thyroid hormone stimulating efficacy of Acacia senegal (Gum Arabic) bark extract in 6-n-propyl-2-thiouracil (PTU)-induced hypothyroid albino rats. Methods: Ethanolic extract of A. senegal bark was given to PTU-induced hypothyroid albino rats at the dose of 500 mg/kg body weight. The animals were divided into control, PTU, and A. senegal bark extract treated and standard drug Eltroxin-treated groups for 60-day experimentation. The serum thyroxin levels, organ's weight, and serum biochemistry were carried out. Results: Oral administration of A. senegal bark extract caused a highly significant increase (pâ‰¤0.001) in serum triiodothyronine (T3) and tetraiodothyronine (T4), and significant changes were also observed in organ's weight with biochemical parameters as compared to hypothyroid albino rats and results were approximate to the standard drug Eltroxin. Conclusion: These results evaluate that ethanolic extract of A. senegal bark helps to compensate or increases the serum thyroxin level in management of hypothyroidism.